The Image of Central European Immigrant in Popular Fiction and Its Adaptations: A Case Study of the Detective Murdoch/Murdoch Mysteries Series - Biljana Oklopcic (European Journal of American Studies)
Popular fiction is often defined as formula fiction as it tends to employ a much more limited repertory of plots, characters, and settings than Literature. Westerns, fantasies, romances, mysteries, science fiction, adventures, etc. must have a certain kind of setting, a particular cast of (stereotypical) characters, and follow a limited number of lines of action because of their close connection to a particular society, culture, and time period. Although appealing to a great number of readers, this limited repertory of (stereotypical) characters, plots, and settings is founded on a canonized discourse, resting on a cultural and social personification—a description, a code, a projection, which legitimizes and authorizes the interpretation of culture and nature, masculinity and femininity, superiority and inferiority, power and subordination, therefore reflecting specific cultures’ interests, values, beliefs, and tensions, and implicitly or explicitly providing insights into specific cultures’ anxieties and aspirations. The aim of this paper is to examine (1) how the mystery formula in Canadian popular print and TV media constructs the image of Central European immigrant and (2) to what extent the mystery formula in Canadian popular print and TV media relies on stereotypes to create entertainment with rules known to everyone, allowing them to participate in its models of suspense and resolution. The analysis focuses on Maureen Jennings’s Detective Murdoch series (Except the Dying (1997), Poor Tom Is Cold (2001), and Vices of My Blood (2006)) and its TV adaptation Murdoch Mysteries (2008–).